2022
DOI: 10.1002/jsfa.12225
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of biogenic amine during broad bean paste fermentation: microbial diversity and functionality via Bacillus bioaugmentation

Abstract: BACKGROUND: Broad bean paste is a high nitrogen and high salt traditional Chinese condiment, which triggers biosynthesis of nitrogen hazards like biogenic amines (BAs). Mechanisms of association and applied research of functional safety and community assembly within multiple-microbial fermentation are currently lacking. Here, bioaugmentation was performed based on the profiles of BAs accumulation and microbial succession to evaluate the functional variation within broad bean paste fermentation.RESULTS: Putresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(93 reference statements)
0
7
0
Order By: Relevance
“…Biogenic amine (BA) concentrations were assessed using HPLC equipped with a diode array spectrophotometer (Hitachi, Japan) . Five milliliter samples were pretreated by adding 25 mL of 0.1 M hydrochloric acid in 50 mL centrifuge tubes, followed by centrifugation at 6000 g for 10 min to collect the supernatants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biogenic amine (BA) concentrations were assessed using HPLC equipped with a diode array spectrophotometer (Hitachi, Japan) . Five milliliter samples were pretreated by adding 25 mL of 0.1 M hydrochloric acid in 50 mL centrifuge tubes, followed by centrifugation at 6000 g for 10 min to collect the supernatants.…”
Section: Methodsmentioning
confidence: 99%
“…Biogenic amine (BA) concentrations were assessed using HPLC equipped with a diode array spectrophotometer (Hitachi, Japan). 30 Five milliliter samples were pretreated by adding 25 mL of 0.1 M hydrochloric acid in 50 mL centrifuge tubes, followed by centrifugation at 6000g for 10 min to collect the supernatants. A 2 mL supernatant was mixed with 0.2 mL of an internal standard (100 g L −1 , 1,7-diaminoheptane) and then underwent derivation with dansyl chloride (Merck, Darmstadt, Germany).…”
Section: Propagated Experiments On Triple Competitive Combinationsmentioning
confidence: 99%
“…Five functional fermentative strains of A. oryzae, B. subtilis, S. gallinarum, W. confusa, and Zygosaccharomyces rouxii were identified by correlation analysis of stress tolerance, bacteriostatic and metabolic properties, and the SynComs constructed by them was used to keep the salinity at 6%. Spermine, putrescine, and spermidine were the primary biogenic amines found in broad bean paste; the addition of salt water caused a gradual decrease in the biogenic amine content (Luo et al, 2023). Luo et al (2023) hypothesized that salinity affected the amine oxidase microorganisms in the fermentation system, leading to a decrease in biogenic amine content.…”
Section: Beanmentioning
confidence: 99%
“…Spermine, putrescine, and spermidine were the primary biogenic amines found in broad bean paste; the addition of salt water caused a gradual decrease in the biogenic amine content (Luo et al, 2023). Luo et al (2023) hypothesized that salinity affected the amine oxidase microorganisms in the fermentation system, leading to a decrease in biogenic amine content. Subsequent work on the prediction of microbial function revealed that Bacillus spp.…”
Section: Beanmentioning
confidence: 99%
See 1 more Smart Citation